Integrating Islamic Personality Values Into Information And Communication Technology Learning At SMP Unggulan Qur'an Tumijajar - Muhfidz Khoirul Anam; Ehwanudin Ehwanudin; Hanif Amrulloh (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
The purpose of this study is to describe in depth the integration of Islamic personality values in Information and Communication Technology (ICT) learning at SMP Unggulan Qur’an Tumijajar. This research is motivated by the rapid development of the digital era, which brings various challenges to students’ behavior and morality, such as low digital ethics, tendencies toward plagiarism, and a lack of responsibility in the use of technology. Therefore, it is necessary to implement learning strategies that not only focus on technical aspects but also instill Islamic values such as honesty (shiddiq), responsibility (amanah), and proper conduct (adab) in digital interactions. This study employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation, while data analysis is conducted through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the integration of Islamic values in ICT learning can be effectively carried out through contextual learning strategies, teacher role modeling, and the habituation of positive behavior in technology use, which in turn enhances students’ awareness of digital ethics, strengthens academic responsibility, and fosters Islamic character in learning activities. In conclusion, ICT learning plays a strategic role not only in improving technological competence but also as an effective medium for shaping students’ character and Islamic personality in the midst of the digital era